Beyond immunohistochemistry and immunocytochemistry: a current perspective on galectin-3 and thyroid cancer. Issue 12 (2nd December 2019) - Li, Jennifer; Vasilyeva, Elizaveta; Wiseman, Sam M.
ABSTRACT: Introduction : Thyroid nodules are very common in the general population, most are benign, and do not require any intervention. However, often a challenge exists in discriminating benign thyroid nodules from cancer, without performing a biopsy or operation. Galectin-3 is a beta-galactoside binding protein that is involved in diverse biological processes and has been found to have increased expression in many human cancer types including thyroid cancer. As a result, recent studies have investigated its utility as a serum biomarker for thyroid cancer, as well as a novel target for in vivo molecular imaging of cancer. Additionally, given its role in tumorigenesis and cancer progression, galectin-3 targeting is currently under investigation for its potential utility as treatment for thyroid cancer. Areas covered : Recent studies of galectin-3 as a serum marker for thyroid cancer diagnosis, and in the preclinical setting as a target for cancer imaging and therapy. Expert opinion : Even though current studies evaluating galectin-3 as a serum marker and target for cancer imaging and therapy are promising, further research is required before it can be adopted into routine clinical use.